LOVES’S METAPHORICAL LANDSCAPE: A CONCEPTUAL ANALYSIS OF SHAKESPEARE’S SONNETS - Purwadi, Purwadi (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2024)
Abstract. This study analyses Shakespeare's construction of love and beauty in his sonnets through the lens of conceptual metaphor theory (CMT). Shakespeare's sonnets, particularly the 1609 Quarto, offer a rich source for exploring his poetic representation of complex emotions and abstract concepts. CMT, developed by Lakoff and Johnson, provides a framework for understanding how we conceptualize abstract domains through concrete source domains via systematic metaphorical mappings. This study examines eight sonnets, selected for their thematic relevance and metaphorical density, exploring how Shakespeare utilizes and adapts conventional metaphorical systems to express his unique vision of love and beauty. The analysis focuses on two overarching themes: the immortalization of beauty through art and the transient nature of love and beauty subject to time's passage. Through close reading and interpretive analysis, the study identifies key metaphors and analyses their source and target domains, mapping the conceptual correspondences that shape Shakespeare's poetic expression. The findings reveal Shakespeare's versatile use of source domains, drawing from nature, celestial bodies, art, time, and human relationships, to convey the complexities of love and beauty. While some sonnets adhere to established metaphorical conventions, others playfully subvert them, enriching his poetic voice and creating layers of meaning. This study illuminates the cognitive and cultural underpinnings of Shakespeare’s artistic choices, demonstrating how he employs conceptual metaphors to engage with fundamental human experiences and reflect the Elizabethan worldview. The research contributes to a deeper understanding of Shakespeare’s poetic genius and the enduring power of his sonnets by revealing how metaphorical language shapes our understanding of abstract concepts. Keywords: Beauty; Conceptual metaphor theory; Love; Shakespeare's sonnets